Taguchi and morphological analysis on the lubricated friction and wear of titanium alloy Ti10V2Fe3Al under CNT nano-lubricant - Lubis, Abdul Munir Hidayat Syah; Abdullah, Muhammad Ilman Hakimi Chua; Puspitasari, Poppy; Permanasari, Avita Ayu; Pramono, Diki Dwi (Malaysian Tribology Society (Mytribos), 2024)
Due to low surface oxides and plastic shearing, titanium alloys known to have low tribological properties and application of lubricants can improve these properties. This work aims to study the effect of CNT's type, load, and sliding speed on lubricated friction and wear of Titanium Alloy Ti10V2Fe3Al by Taguchi method and wear surface morphology under the CNT nano lubricants. Titanium alloy Ti 10V2Fe3Al pin was rubbed against a steel disc. Samples of nano lubricants were made from commercial oil infused with 1 ppm SWCNT's, DWCNT's, and MWCNT's. The relationship between CNT's type, testing load, and speed, to friction and wear of the Ti10V2Fe3Al is examined using Taguchi's method. The result of present work suggests that variability on friction and wear of Ti 10V2Fe3Al are most affected by the load. The SWCNT’s nanolube shall provide smaller variability to friction but the MWCNT's nanolube gives smaller variability to wear. Intermediate rubbing speed gives smaller variability to friction and high rubbing speed gives smaller variability to wear. Load and speed can cause CNTs to roll, exfoliate the structure, and absorb titanium surface to form a protective mechanism. Despite presence of nano lubricant, the adhesive wear may still dominantly occur.